2022
DOI: 10.1007/s10389-022-01716-0
|View full text |Cite
|
Sign up to set email alerts
|

Closing the “happiness gap” by closing the wealth gap: the role of wealth on life satisfaction between east and west-Germans

Abstract: Background In Germany there is a large wealth gap between East and West Germans as well as a gap in life satisfaction, with people in East Germany reporting to be less satisfied. This paper intends to shed light on the role of the different levels of wealth and their association with life satisfaction. On a wider scale, this paper examines psychological consequences of wealth inequality between large societal groups. Method Longitudinal data from the years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
1
3
0
1
Order By: Relevance
“…While the ordered probit model is commonly used in happiness studies, Ferrer-i-Carbonell and Frijters (2004) have noted that OLS regression can yield results comparable to those of the ordered probit model in this context. This approach is also consistent with earlier research in this field, such as the works of Gao et al (2022) and Kasinger et al (2023) , who used linear regression models in their analyses.…”
Section: Methodssupporting
confidence: 88%
See 2 more Smart Citations
“…While the ordered probit model is commonly used in happiness studies, Ferrer-i-Carbonell and Frijters (2004) have noted that OLS regression can yield results comparable to those of the ordered probit model in this context. This approach is also consistent with earlier research in this field, such as the works of Gao et al (2022) and Kasinger et al (2023) , who used linear regression models in their analyses.…”
Section: Methodssupporting
confidence: 88%
“…This perspective suggests that wealth may be an overlooked factor in prior income–happiness studies, as low income does not necessarily equate to low wealth, and wealth impacts happiness in more ways than income alone. Supporting this view, Kasinger et al (2023) found that net wealth is a significant predictor of life satisfaction, based on data from the German Socio-Economic Panel (GSOEP). Nonetheless, research in the area of wealth and happiness remains relatively limited.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…A lower level of income ( Table 1 ), high rates of unemployment, respectively premature pension decrease satisfaction with income and with work. Recently, we could show that wealth is predictive of life satisfaction ( 20 ). The still-increasing wealth gap clearly acts in favor of the wealthier inhabitants of the Western states.…”
Section: Discussionmentioning
confidence: 99%
“…Auch wenn sich die Löhne und das Haushaltseinkommen in Ostdeutschland verbessert und dem Westen angenähert haben, gibt es dennoch signifikante Unterschiede, wobei die Ostdeutschen nach wie vor weniger verdienen [16]. Ein weiterer Aspekt, der sicherlich zur finanziellen Unzufriedenheitslücke beiträgt, sind die sehr ungleich verteilten Vermögenswerte zwischen Ost-und West-deutschland, die ebenfalls einen Einfluss auf die Lebenszufriedenheitsunterschiede haben [23]. Nichtsdestotrotz sind wohl besonders die verbesserten ökonomischen Lebensbedingungen für die stetige Verbesserung der allgemeinen und bereichsspezifischen Lebenszufriedenheit verantwortlich.…”
Section: Diskussionunclassified